2023
DOI: 10.3390/catal13030565
|View full text |Cite
|
Sign up to set email alerts
|

A Molybdenum(VI) Complex of 5-(2-pyridyl-1-oxide)tetrazole: Synthesis, Structure, and Transformation into a MoO3-Based Hybrid Catalyst for the Epoxidation of Bio-Olefins

Abstract: The discovery of heterogeneous catalysts synthesized in easy, sustainable ways for the valorization of olefins derived from renewable biomass is attractive from environmental, sustainability, and economic viewpoints. Here, an organic–inorganic hybrid catalyst formulated as [MoO3(Hpto)]·H2O (2), where Hpto = 5-(2-pyridyl-1-oxide)tetrazole, was prepared by a hydrolysis–condensation reaction of the complex [MoO2Cl2(Hpto)]∙THF (1). The characterization of 1 and 2 by FT-IR and Raman spectroscopies, as well as 13C s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Recently, the Lindqvist-type POM [tBu-Hptz] 2 [Mo 6 O 19 ] (tBu-Hptz = 2-tert-butyl-5-(2-pyridyl)tetrazole) was studied as epoxidation catalysts using readily available and relatively ecofriendly hydroperoxide oxidants (hydrogen peroxide and tertbutyl hydroperoxide). 87 This POM acted as a homogeneous catalyst and could be recycled by employing an IL solvent. It was found that the type of anion of the IL could affect the catalytic performance.…”
Section: The Catalytic Oxidationmentioning
confidence: 99%
“…Recently, the Lindqvist-type POM [tBu-Hptz] 2 [Mo 6 O 19 ] (tBu-Hptz = 2-tert-butyl-5-(2-pyridyl)tetrazole) was studied as epoxidation catalysts using readily available and relatively ecofriendly hydroperoxide oxidants (hydrogen peroxide and tertbutyl hydroperoxide). 87 This POM acted as a homogeneous catalyst and could be recycled by employing an IL solvent. It was found that the type of anion of the IL could affect the catalytic performance.…”
Section: The Catalytic Oxidationmentioning
confidence: 99%
“…A bidentate NO coordination with molybdenum (VI) is formed during catalyst formations. Catalytic study is done on epoxidation of several compounds such as cis‐cyclooctene (90% yield at 6 h), biobased olefins (linolenates, limonene diol, and monoepoxide), sulfide (methylphenylsulfide and diphenylsulfide) 112 . Zhang et al synthesized vitrimers from castor oil by introducing an epoxy group with a CC double bond.…”
Section: Factor Affecting Epoxidationmentioning
confidence: 99%
“…For HOOH, the following complexes were used: cobalt sandwich-type polyoxometalates [39], tungstophosphates [2], polyoxotungstates [11], Schiff base complexes with Co(II) and Cu(II) and the same compounds but immobilized in zeolite-Y [40], manganese(II) acetylacetonate on MCM41 [41], Al 2 O 3 [42], the ions of non-transition metal [1], methyltrioxorhenium with different ligands [43], activated carbon where the active phase was the magnetite Fe 3 O 4 [44] or MoO 2 [45], complexes of VO and copper(II) with Schiff base ligands entrapped in the supercages of zeolite-Y [46], homogeneous and heterogeneous VO and iron(II) with Schiff base ligands [47], γ-Fe 2 O 3 /SiO 2 -NHFeP prepared from nanospheres and 5,10,15,20-tetrakis (pentafluorphenylporphyrin) iron(III) [48], heterogeneous Mn(III), Fe(III), and Co(III) porphyrin-based complexes immobilized on zeolite [49] or others complexes based on zeolite-Y [50][51][52] in which enclosing the catalyst in the porous structure of the support prevents the dimerization of the complexes, ensuring their catalytic activity. Catalysts used with t-butyl hydroperoxide as the oxidant are also zeolites, e.g., zeolite-Y with entrapped VO with Schiff base ligands [50], organic hybrid materials [26,53], Ti-MCM-41, and Ti-MWW compounds [54], iron(II) [55], molybdenum(II) complexes [56], salen-like Jacobsen's catalysts with manganese(III) [57] or carbon-based complexes with cobalt(II) acetylacetonate [58]. Jacobsen's compounds with manganese(III) [59,60] with Mn(II), Ni(II), Co(II) [61], or VO(Salten) anchored on SBA-15 (Salten-3-[N,N ′ -bis-3(salicylidenamino)ethyltriamine]) [62] were also used with other oxidants such as KHSO 5 (used as ozone), iodosylbenzene, sodium hypochlorite, or urea hydroperoxide.…”
Section: Introductionmentioning
confidence: 99%